Reduced impact logging guidelines for Indonesia (Vietnamese) - Elias; Applegate, G.; Kartawinata, K.; Machfudh; Klassen, A. (Center for International Forestry Research, 2005)
The principles and practices for forest harvesting in Indonesia (2000) have been developed to provide a uniform set of minimum standards for logging practices in the production and limited production forests in Indonesia. The provide the standard for WHAT is involved in planning and implementing logging activities in natural forest and WHY certain operations should be undertaken. The Reduced Impact Logging (RIL) guidelines for Indonesia provides the mechanism for HOW the standards will be applied in the field or "how to do the work". Tractor skidding--mostly by crawlers and skidders--is the most common system (ca. 90%) used in the Indonesian Selective Cutting and Planting (TPTI) System. Considering the fact that familiarity with more environmentally friendly logging system (such as cable and aerial logging) is still lacking in Indonesia, often due to cost, etc., RIL guidelines focus on ground-based harvesting which can be implemented in the lowland and hill forests in Indonesia. Target groups of this guidelines are production supervisors, RIL planners, bolck inspectors, road network planners, road construction supervisors, machine operators, chainsaw operators, tractor operators and their assistants.